PENERAPAN METODE PEMBERIAN TUGAS PADA PEMBELAJARAN JARAK JAUH (PJJ) MATA PELAJARAN IPS UNTUK MENINGKATKAN KETUNTASAN BELAJAR SISWA DI SMPN 1 MARGAHAYU KAB. BANDUNG - Euis Ani Arlinah (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2022)
This Classroom Action Research was conducted at SMP Negeri 1 Margahayu class IX-H. the author examines the problems faced by students in social studies learning, especially to achieve complete learning. In this case the author uses the assignment method for online learning or distance learning during the Covid-19 pandemic. The purpose of this study is to see whether the application of the assignment method can help students achieve complete learning. The author held treatment with 3 cycles of learning activities. In the first cycle student learning completeness is worth 62%, namely there are 17 students out of 45 students who have not achieved the KKM value and the assessment in the second cycle of student learning completeness is 77%, namely there are 10 students who have not achieved the KKM value and in the third cycle it increased rapidly to 93 %, namely only 3 people who have not reached the KKM score. From the results of the study, it was concluded that this assignment method was able to help achieve student learning completeness at school.